A Study of Influencing Factors on Online Buyers’ Behaviour in Chengalpattu Town - R.ANEEDHA; T.J.ARUN (International Journal of Psychosocial Rehabilitation, 2020)
The electronic market is growing and an increasing number of young customers seem to be buying the products. With the advertisement in various social media, community groups and government support in cashless India increases the popularity of online shopping. The retailers and wholesalers begin to look for online marketers’ service to market their products. Buyers concern on security issues are reducing and have positive impact on online shopping. The theory of planned behaviour helps to understand the consumer behaviour. The research study focuses on influencing factors of buyers’ behaviour on online purchases. To know the buyers behaviour on online purchases, the questionnaire was framed based on the objectives of the study and the data collection was carried out in Chengalpattu district.